Full Endoscopic Technique for High-Grade Up-Migrated Lumbar Disk Herniation via a Translaminar Keyhole Approach: Preliminary Series and Technical Note - Lin, Guang-Xun; Park, Cheul-Woong; Suen, Tsz-King; Kotheeranurak, Vit; Jun, Su-Gi; Kim, Jin-Sung (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Aims Technically and anatomically, accessing a high-grade migrated lumbar disk herniation (LDH) using traditional full endoscopic lumbar diskectomy (FELD) approaches (either transforaminal or interlaminar) is challenging. The objective of this study was to present an effective and safe surgical approach for high-grade up-migrated LDH by translaminar FELD.Patients and Methods Thirteen patients with soft high-grade up-migrated LDH treated with a translaminar FELD between May 2015 and July 2018 were reviewed in this study. Five of these patients had very high-grade up-migration. Clinical outcomes were assessed including preoperative and postoperative visual analog scale (VAS) for back and leg pain, Oswestry Disability Index (ODI), and MacNab criteria.Results Overall, 7 of the 13 patients had disk-fragment migration at L4–L5: three at L5–S1, two at L3–L4, and the remaining one at L2–L3. In all cases, the highly up-migrated LDH was removed successfully through the translaminar approach, as confirmed by postoperative magnetic resonance imaging. The improvements of VAS for back and leg pain were 4.5 ± 0.9 to 1.3 ± 1.3 and 7.1 ± 1.0 to 1.6 ± 0.7, respectively (both p < 0.05). The ODI decreased from preoperative 41.9 ± 6.0 to postoperative 13.0 ± 4.1 (p < 0.05). According to the MacNab criteria, the satisfaction rate was 92.3% (excellent or good outcomes). None of the patients experienced any perioperative complications or recurrence during the follow-up period.Conclusion Although full endoscopic technique via the translaminar keyhole route may not be used as a routine surgical approach, it could serve as a feasible alternative method for patients with highly up-migrated disk herniation.
Keywords: translaminar; full endoscopic lumbar diskectomy; migrated disk herniation; lumbar spine